Modern Slavery in Global Supply Chains: A Case Study Review of the Firm Practices for a More Responsible Procurement - Sirin, Beril (2018)
Modern slavery is a term we often meet but we do not even know what we hear really exists in practice. The fact that the employees of the emerging country suppliers of the leading firms may work under sweatshop-like conditions for our favorite clothing brand, or child labour is dominantly exploited in cocoa or chocolate production, or the people brought in from other countries to work in unethical conditions may not be familiar but true and widespread more than ever. Today's wealthy global companies have a dark reason behind the cheap products they serve and this is forced labour business model. This study tries to explore how important collaboration is in solving all these problems by looking at the darkest and most secretive aspects of today's supply chains: Modern slavery will be examined in light of the hazardous business models, cooperation with the Non-Governmental Organisations and transparency, along with the recommendations will be provided by the case studies reviewed.